METHODS OF IMPLEMENTATION IN EDUCATIONAL PROCESS INNOVATIVE TEACHING TECHNOLOGIES - Usmanova Аzizakhon Аbdullajonovna (Educational Research in Universal Sciences, 2023)
The article is focused on new ways and methods of implementation of innovative pedagogical technologies in educational programs of universities. In this connection, it emphasizes the priority of modular training system. Reveals the essence and content of the module as a structure of the educational program, in which we study several disciplines, courses and sections of Sciences. It specifies technology of application modules including complex methods of problem-based learning, electronic development manuals, e-learning programs, joint project work involving actualization of creativity and self-activity of students.